STEGANOGRAPHY CAPACITY ANALYSIS OF TEXT IN TEXT WITH SENTENCE STRUCTURE IN INDONESIAN - Siahaan, R. Fanry; Sitohang, Amran; Febrian, Ibnu; Putri, Widia (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2022)
Data security issues become very important when the computer has been used as a communication tool on a global network (internet). One method that is quite popular for securing data from irresponsible parties is text-based steganography, where confidential data or information is hidden or inserted into other text media so as not to arouse suspicion from other parties. Based on the input data calculated on the number of words, it has a significant influence on the results of the stegotext. This can be seen from the comparison of the length of the input message which is calculated in the number of words with the length of the output message (stegoteks) which is influenced by the length of the style (pattern) of the sentence structure used. For input data with a word length of 1, the average capacity of the stegotext is 8 to 9 words or 12.4%, for input word length 2, the average capacity of the stegotext is 22 words or 8.85% and the input word length is 4 then the capacity of the stegotext is between 30 to 33 words or equivalent to 12.91%. Keywords :Text Steganography; Sentence Pattern; Payload Balancing Capacity